Can Quotas Increase the Supply of Candidates for Higher-Level Positions? Evidence from Local Government in India - Stephen D. O'Connell (Institute of Labor Economics (IZA), 2018)
A common argument for quota policies is that they can increase the participation of targeted groups in positions that are not directly subjected to quotas or after quotas are no longer in place. I investigate this hypothesis empirically in the context of India, where one third of local political leadership seats are randomly assigned to be held by a woman in each election cycle. Quotas increase the number of female candidates who later contest seats in state and national legislatures, where such policies do not exist. This effect arises from the candidacy of beneficiaries who gained experience in local government due to the quotas and career politicians who continue contesting in longer-exposed areas. Effect magnitudes imply that the policy accounts for a substantial portion of the increase in female candidates for these bodies since the start of the policy. The new candidates have a higher probability of a top finish when they run on major party tickets or contest in areas where the local constituency overlaps closely with that of the contested seat.
Keywords: J15; J45; 330; quotas; affirmative action; political candidacy; India